Kasus Pure Red Cell Aplasia Sebagai Komplikasi Terapi Tuberkulosis Pulmonal - Abram P Tanuatmadja; Limdawati Kwee; Fellicia Tan; Ardo Sanjaya; Julia W Gunadi (Journal of Medicine and Health, 2023)
Pure red cell aplasia (PRCA) is a rare disorder caused by failure or abnormalities in erythropoiesis only, among all cell lines of the bone marrow. Patients with PRCA usually present with no specific clinical presentation, thus its recognition depends on a clinician’s high index of suspicion, to facilitate early diagnosis and treatment to provide a better prognosis. Tuberculosis (TB) is the infectious disease with the highest casualty rate worldwide and is still a problem in many countries, including Indonesia. This study is a case report of a pulmonary TB patient with PRCA as a complication. PRCA was confirmed by the bone marrow puncture (BMP) examination as the gold standard. In this case, PRCA was inferred to occur due to the use of Isoniazid in the TB treatment regimen. The discontinuation of Isoniazid administration subsequently results in the normalization of Hb levels. In this paper we would highlight PRCA as a differential diagnosis that should be taken into consideration in symptomatic anemia in patients with tuberculosis under standard treatment.